2020
DOI: 10.1007/978-3-030-27874-8_6
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Infection Prevention and Control (IPC) and Antimicrobial Stewardship (AMS): Dual Strategies to Reduce Antibiotic Resistance (ABR) in Hospitals

Abstract: In this chapter we review the development of hospital infection prevention and control (IPC) since the nineteenth century and its increasingly important role in reducing the spread of antibiotic resistance (ABR). Excessive rates of hospital-acquired infection (HAI) fell dramatically, towards the end of the nineteenth century, because of improved hygiene and surgical antisepsis, but treatment remained rudimentary until effective antibiotics became widely available in the mid-twentieth century. While antibiotics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 116 publications
(117 reference statements)
0
5
0
Order By: Relevance
“…Moreover, continuous monitoring and feedback have been found to be effective strategies to enhance hand hygiene adherence [ 40 ]. In past research in our laboratory [ 19 , 21 ], we have found that while training and intervention improved student participant knowledge and attitudes about hand hygiene, their actual practices, as evidenced by microbial data from their hands, did not align with their knowledge and attitudes. We deduced that the presence of bacteria on the hands could be a result of inadequate hand hygiene practice rather than a lack of hand hygiene frequency.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Moreover, continuous monitoring and feedback have been found to be effective strategies to enhance hand hygiene adherence [ 40 ]. In past research in our laboratory [ 19 , 21 ], we have found that while training and intervention improved student participant knowledge and attitudes about hand hygiene, their actual practices, as evidenced by microbial data from their hands, did not align with their knowledge and attitudes. We deduced that the presence of bacteria on the hands could be a result of inadequate hand hygiene practice rather than a lack of hand hygiene frequency.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, the frequency of each reason does not necessarily reflect its significance or impact on overall hand hygiene practices. Several factors have been reported to negatively impact adherence to recommended practices among HCWs [ 20 , 21 , 22 , 23 , 52 ]. These factors include limited knowledge and awareness, handwashing agents causing discomfort and dryness, inconveniently positioned sinks, a lack of soap and paper towels, time limits, severe workload owing to understaffing, unfamiliarity with rules and practices, and occasional forgetfulness [ 10 , 18 , 20 , 22 , 44 , 52 , 53 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the many challenges of AM stewardship, one possible framing is in terms of intergenerational justice: how to appropriately balance the wellbeing of current and future patients [ 128 ]. Variably termed appropriate, prudential, or rational use of AMs, stewardship is also often understood as a classic challenge of implementation science; evidenced-based standards of AM use are established, but integrating this knowledge into practice is no simple matter [ 129 ]. Behavior change is notoriously challenging for humans, including experts.…”
Section: Amr Is Distinct: Toward An Elsi Of Precision Antimicrobial S...mentioning
confidence: 99%
“…Reducing person-to-person transmission involves implementing various measures to minimize the spread of infections between patients, healthcare workers, and visitors. This includes promoting proper hand hygiene practices (i.e., handwashing or using hand sanitizers), and practicing safe injection practices [ 11 ]. On the other hand, preventing transmission from the environment involves maintaining a clean and hygienic healthcare setting.…”
Section: Introductionmentioning
confidence: 99%